PENDIDIKAN MULTIKULTUR DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK DAN BUDI PEKERTI SEBAGAI UPAYA MENGHARGAI KEBERAGAMAN SISWA KELAS VII E SMP NEGERI 13 PONTIANAK - Nani, Marta; Kurniati, Yusi; Tinenti, Hemma Gregorius (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2025)
This study aims to describe the learning process and inhibiting factors of Multicultural Education in Catholic Religious Education and Character Education learning in Class VII E of SMP Negeri 13 Pontianak. Using a qualitative descriptive method with interview and documentation techniques, the study involved one Catholic Religious Education teacher, four students, and one principal as data sources. The results of the study indicate that multicultural education has been integrated into learning even though there is no specific theme about multicultural education. Teachers insert values ​​of respect for differences in gender, ethnicity, culture, and religion in the learning process. Teachers also act as role models by showing an attitude of respecting differences inside and outside the classroom. The main inhibiting factors are the lack of facilities and infrastructure such as narrow rooms, the unavailability of tables, chairs, blackboards, and learning books, and the lack of socialization activities about multicultural education. This study recommends improving facilities and infrastructure and the intensity of socialization to optimize multicultural education in schools.